Recombinant parechovirus A3 possibly causes various clinical manifestations, including myalgia; findings in Yamagata, Japan in 2019. Issue 9 (2nd September 2022) - Mizuta, Katsumi; Itagaki, Tsutomu; Chikaoka, Shuji; Wada, Manabu; Ikegami, Toru; Sendo, Dai; Iseki, Chifumi; Shimizu, Yukitoshi; Abe, Shuichi; Komabayashi, Kenichi; Aoki, Yoko; Ikeda, Tatsuya
Abstract: Background: Parechovirus A3 was first reported in 2004 and has been recognized as a causative agent of mild and severe infections in children. Since we first reported an outbreak of adult parechovirus A3-associated myalgia in Yamagata, Japan in 2008, this disease has since been recognized across Japan, but has not yet been reported from other countries. Aim: We analysed 19 cases of parechovirus A3 infections identified in Yamagata in 2019 to further clarify the epidemiology of this disease. Methods: We performed phylogenetic analyses of parechovirus A3 isolates and analysed the clinical manifestations and the genomic clusters. Results: There were two clusters, with cluster 2019B replacing 2019 A around October/November. Phylogenetic analysis revealed that 2019B cluster strains and Australian recombinant strains, which appeared between 2012 and 2013, were grouped in one cluster at non-structural protein regions, suggesting that the ancestor to these regions of 2019B cluster strains were Australian recombinant lineage strains. The strains from both clusters caused various infections in children including myalgia. These findings strongly support that parechovirus A3 strains cause myalgia and other paediatric infections irrespective of the virus strains involved, including recombinant strains.　　 Conclusions: We have reported repeatedly sporadic cases of myalgia and here showed that recombinant strains also cause myalgia. We hope our experiences will help better understand these infections and possibly result in detection of more cases in the world.